PENINGKATAN KINERJA SISTEM E-LEARNING DALAM PERSPEKTIF UNIVERSITAS 4.0 MENGGUNAKAN KERANGKA IT BALANCED SCORECARD - Syafitri, Nadidah Ayu; Herdiansyah, Muhammad Izman (Gema Teknologi, 2020)
Bina Darma University (UBD) as one of the university based information technology currently has been assisted by the use of IT in implementing its strategy. University 4.0 is a university that makes students as a learning center and assisted by the use of IT.Â  UBD in conducting learning has been assisted by e-learning which is one of the benchmarks of 4.0 University perspectives. E-Learning implementation assists the learning process by students and lecturers. The performance of the e-learning system has not been measured. Measurements are performed to improve the quality of e-learning systems in the 4.0 university perspective. To perform analysis used the IT framework Balanced Scorecard consisting of four perspectives namely Corporate Contribution/Business Contribution, User Orientation, Operational Excellence and Future Orientation. The result of this research is an improved analysis of quality and strategies to improve the quality of e-learning systems in the 4.0 university perspective.